Review of the “Oncology 2.0” Textbook under the Editorship of Professor Sh.Kh. Gantsev - I. R. Rakhmatullina (Креативная хирургия и онкология)
The textbook “Oncology 2.0” by K.Sh. Gantsev, Sh.R. Kzyrgalia, F.V. Moiseenko, and R.S. Yamidanov, under the editorship of Professor Sh.Kh. Gantsev follows the history of the authors’ publications for more than 20 years, revealing the mechanisms of the modern concept of carcinogenesis as one of the conditions for successful diagnostics and treatment in oncology. This is particular relevant under contemporary conditions, when oncology is becoming an increasingly knowledge-intensive discipline and requires competence in various fields of science to be synthesized for its successful development. The textbook successfully accomplished the task of academic presentation of complex material in a simple form, combining extensive knowledge of molecular biology, genetics, clinical and experimental oncology, anatomy, lymphology, as well as with own unique scientific developments.